Private sector operations in 2020 report on development effectiveness. (Manila Asian Development Bank, 2021)
The Private Sector Operations Report on Development Effectiveness series reviews the development effectiveness of ADB private sector operations. Aside from an overview of COVID 19 responses, the 11th edition of the report also focuses on initiatives in line with the priorities laid out under ADB Operational Plan for Private Sector Operations, 2019 to 2024.
Keywords: Sustainable development; Economics; Electronic books